Comparative analysis of assessment methods in the history of pedagogy (MMIT Proceedings, 2025)
The article discusses the main methods of assessing students' knowledge, used in differenthistorical periods of the development of pedagogical science. A comparative analysis of traditional andmodern approaches to assessment has been carried out, their strengths and weaknesses have been identified.The key changes in approaches to assessing academic achievements from oral exams to a competencybased approach are presented. Special attention is paid to the influence of the socio-cultural context on thechoice of assessment strategies